2022
DOI: 10.3390/en15145081
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Long-Term Performance of Proton Exchange Membrane Fuel Cells: From Degradation Modeling to the Effects of Bipolar Plates, Sealings, and Contaminants

Abstract: Proton-exchange membrane fuel cells (PEMFCs) are regarded as promising alternatives to internal combustion engines (ICEs) to reduce pollution. Recent research on PEMFCs focuses on achieving higher power densities, reducing the refueling time, mitigating the final price, and decreasing the degradations, to facilitate the commercialization of hydrogen mobility. The design of bipolar plates and compression kits, in addition to their coating, can effectively improve performance, increase durability, and support wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…A dynamic compression test was carried out to observe the plastic strain, cyclic loading, and relaxation in long-term durability since fuel cells frequently are assembled and dismantled throughout their lifespan. Under this circumstance, there can be fatigue failures of active components such as membranes, electrodes, gas diffusion layer, and BPs [ 66 ]. Figure 8 illustrates hysteresis loops gained from 1000 loading and unloading with compressive force.…”
Section: Resultsmentioning
confidence: 99%
“…A dynamic compression test was carried out to observe the plastic strain, cyclic loading, and relaxation in long-term durability since fuel cells frequently are assembled and dismantled throughout their lifespan. Under this circumstance, there can be fatigue failures of active components such as membranes, electrodes, gas diffusion layer, and BPs [ 66 ]. Figure 8 illustrates hysteresis loops gained from 1000 loading and unloading with compressive force.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the cooling plates are made of either graphite or metallic materials. The most commonly used metallic materials are stainless steel, aluminum, titanium and its alloys [5]- [8]. The flow channels are machined when graphite is used as cooling plate.…”
Section: Figure 1 Pem Fuel Cell Components and Coolingmentioning
confidence: 99%
“…It was discovered that the hydrophobicity of the GDL and MPL impedes the cation solution from reaching the catalyst-coated membrane (CCM). In 2022, Pourrahmani et al 17 conducted an experimental analysis of the mechanism of contamination and the degree of toxicity of ions. They demonstrated that the presence of foreign cations can contaminate the PEM and cause degradation of membrane electrode performance.…”
Section: Introductionmentioning
confidence: 99%